2019
DOI: 10.1177/2050312118822912
|View full text |Cite
|
Sign up to set email alerts
|

How handling missing data may impact conclusions: A comparison of six different imputation methods for categorical questionnaire data

Abstract: Objectives:Missing data is a recurrent issue in many fields of medical research, particularly in questionnaires. The aim of this article is to describe and compare six conceptually different multiple imputation methods, alongside the commonly used complete case analysis, and to explore whether the choice of methodology for handling missing data might impact clinical conclusions drawn from a regression model when data are categorical.Methods:In addition to the commonly used complete case analysis, we tested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 55 publications
(74 reference statements)
1
48
0
Order By: Relevance
“…However, sex differences and time trends were similar to those observed in our primary analysis. The combination of MMSE and PFAQ scores which we used are a more accurate screening tool of CI for the Chilean older population than MMSE alone [19]. We found an increase in LE free of CI and a decrease in LE with CI between 2003 and 2016–17.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, sex differences and time trends were similar to those observed in our primary analysis. The combination of MMSE and PFAQ scores which we used are a more accurate screening tool of CI for the Chilean older population than MMSE alone [19]. We found an increase in LE free of CI and a decrease in LE with CI between 2003 and 2016–17.…”
Section: Discussionmentioning
confidence: 97%
“…This instrument was derived from a previously validated version of the MMSE [18]. Quiroga et al [19] showed that a combination of MMSE and the Pfeffer Functional Activities Questionnaire (PFAQ) had a higher sensitivity and specificity to detect CI among the Chilean older population. Hence, the criteria used to determine if participants had CI were MMSE< 13 and PFAQ≥6.…”
Section: Methodsmentioning
confidence: 99%
“…Besides the problem of small samples sizes, there is also a striking heterogeneity in statistical methods used for missing data imputation and model building (Cohen et al, 2019;. This is of importance since there is evidence that different methods of data imputation and model building may lead to differences in clinical conclusions (Cohen et al, 2019;Stavseth et al, 2019;Webb et al, 2020). However, comparisons between the STEPd PAI model built in 2015 (Huibers et al, 2015) and the PAI model in the present paper that used different methods on the same dataset, indicate significant overlap between selected pre-treatment variables and similar effect sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Model selection was performed with the minimisation of the Akaike information criteria in order to account for possible interactions among variables. In the regression analyses, missing data were imputed using random forests, which is a superior method of imputation for non-parametric variables and when there are many variables in the study 34…”
Section: Methodsmentioning
confidence: 99%